Local food environments are associated with girls' energy, sugar-sweetened beverage and snack-food intakes. Issue 10 (12th May 2014) - Deierlein, Andrea L; Galvez, Maida P; Yen, Irene H; Pinney, Susan M; Biro, Frank M; Kushi, Lawrence H; Teitelbaum, Susan; Wolff, Mary S
Abstract Objective To describe availability and frequency of use of local snack-food outlets and determine whether reported use of these outlets was associated with dietary intakes. Design Data were cross-sectional. Availability and frequency of use of three types of local snack-food outlets were reported. Daily dietary intakes were based on the average of up to four 24 h dietary recalls. Multivariable linear regression models estimated average daily intakes of energy, sugar-sweetened beverages (SSB) and snack foods/sweets associated with use of outlets. Setting Multi-site, observational cohort study in the USA, 2004–2006. Subjects Girls aged 6–8 years (n 1010). Results Weekly frequency of use of local snack-food outlets increased with number of available types of outlets. Girls with access to only one type of outlet reported consuming food/beverage items less frequently than girls with access to two or three types of outlets (P <0·001). Girls' daily energy, SSB and snack foods/sweets intakes increased with greater use of outlets. Girls who reported using outlets>1 to 3 times/week consumed 0·27 (95 % CI 0·13, 0·40) servings of SSB more daily than girls who reported no use. Girls who reported using outlets>3 times/week consumed 449·61 (95 % CI 134·93, 764·29) kJ, 0·43 (95 % CI 0·29, 0·58) servings of SSB and 0·38 (95 % CI 0·12, 0·65) servings of snack foods/sweets more daily than those who reported no use. Conclusions Girls' frequency of use of local snack-food outlets increases with the number of available types of outlets and is associated with greater daily intakes of energy and servings of SSB and snack foods/sweets.